Functionally defining the endothelial transcriptome, from Robo4 to ECSCR. (19th November 2009) - Verissimo, Ana Raquel; Herbert, John M.J.; Heath, Victoria L.; Legg, John A.; Sheldon, Helen; Andre, Maud; Swain, Rajeeb Kumar; Bicknell, Roy
Abstract : We have applied search algorithms to expression databases to identify genes whose expression is restricted to the endothelial cell. Such genes frequently play a critical role in endothelial biology and angiogenesis. Two such genes are the roundabout receptor Robo4 and the ECSCR (endothelial-cell-specific chemotaxis regulator). Endothelial cells express both Robo1 and Robo4, which we have knocked down using siRNA (small interfering RNA) and then studied the effect in a variety of in vitro assays. Both Robo4 and Robo1 knockdown inhibited in vitro tube formation on Matrigel™. Transfection of Robo4 into endothelial cells increased the number of filopodial extensions from the cell, but failed to do so in Robo1-knockdown cells. Separate immunoprecipitation studies showed that Robo1 and Robo4 heterodimerize. We conclude from this and other work that a heteroduplex of Robo1 and Robo4 signals through WASP (Wiskott–Aldrich syndrome protein) and other actin nucleation-promoting factors to increase the number of filopodia and cell migration. Knockdown of the transmembrane ECSCR protein in endothelial cells also reduced chemotaxis and impaired tube formation on Matrigel™. Yeast two-hybrid analysis and immunoprecipitation studies showed that, in contrast with the roundabouts, ECSCR binds to the actin-modulatory filamin A. We conclude that all three of these genes are critical for effective endothelial cell migration and, in turn, angiogenesis.